2011
DOI: 10.4103/0019-509x.92258
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and pathological response rates of docetaxel-based neoadjuvant chemotherapy in locally advanced breast cancer and comparison with anthracycline-based chemotherapies: Eight-year experience from single centre

Abstract: Although pCR rates were higher with docetaxel-based NACT, it did not translate into superior disease-free survival / overall survival compared to anthracycline-based chemotherapies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…7 Taxanes (docetaxel or paclitaxel) have been found to be more effective than anthracylines and have been added in the chemotherapy regimen to get better pathological response. [8][9][10] Aims and objectives of the following study were assessment of effectiveness of neoadjuvant chemotherapy to downstage locally advanced breast cancer based on clinical and radiological findings, selection of surgical procedure according to response to neoadjuvant chemotherapy and to assess the pathological response and to assess the surgical outcome of the procedure.…”
Section: Introductionmentioning
confidence: 99%
“…7 Taxanes (docetaxel or paclitaxel) have been found to be more effective than anthracylines and have been added in the chemotherapy regimen to get better pathological response. [8][9][10] Aims and objectives of the following study were assessment of effectiveness of neoadjuvant chemotherapy to downstage locally advanced breast cancer based on clinical and radiological findings, selection of surgical procedure according to response to neoadjuvant chemotherapy and to assess the pathological response and to assess the surgical outcome of the procedure.…”
Section: Introductionmentioning
confidence: 99%
“…Although there was an overall response rate of 66% with 3 cycles of neoadjuvant CEF, there was no difference in overall or disease free survival between the two arms. Gupta et al found that docetaxel was better then epirubicin in LABC in terms of pCR (Gupta et al, 2011). In our analysis, LABC constituted 37% of all cancers and NACT was admistered in one third of these.…”
Section: Discussionmentioning
confidence: 43%
“…Our study showed an Objective Response (cCR + cPR) rate of 81.25%. OR is reported as 80.4% by Bhattacharyya et al (2014) (2) , 84.4% by Raina V et al (2011), (3) 60.36% by Gupta et al (2011) (7), 86% by Vishwambharan et al (2005), (8) 66% by Deo et al (2003), (10) 80% in NSABP B18 (1997) which included 608 patients showed that patients who received 4 cycles of doxorubicin and cyclophosphamide pre operatively.…”
Section: Total Objective Responsementioning
confidence: 98%
“…Most of the studies (Raina V et al (3), Gupta et al . (7) , Vishwambharan et al . (8) , Egwuonwu et al (9) , Deo et al (2003) (10) ) used 3 to 6 chemotherapy cycles pre-operatively, which is comparable to our study.…”
Section: Chemotherapy Regimensmentioning
confidence: 99%